Influenza vaccine response in community-dwelling German prefrail and frail individuals - Bauer, Jürgen M. (Immunity & ageing, 2017)
The age-related dysregulation of the immune system in older persons results in reduced responses to vaccination and greater susceptibility to infection, especially in frail individuals who suffer the greatest of morbidity and mortality due to infection. Recently, significantly reduced anti-influenza antibody titers and increased rates of influenza infection after vaccination were reported in community-dwelling American frail older adults. The aim of our study was to further assess the relative impact of frailty and of each individual Fried frailty criterion on influenza vaccine response. Prefrail and frail community-dwelling German persons aged ≥70 years were recruited for a nutritional randomized double-blind placebo-controlled clinical trial conducted during the 2014-2015 influenza season. Herein, we present a sub-analysis study of the placebo group to compare 76 prefrail and frail participants.